Heavy metals in some tissues and organs of Common Carp (Cyprinus carpio L., 1758).fish species in relation to body size, age, sex and seasons from Taqtaq Region of Little Zab River, Northern Iraq - Rashid, Rzgar Farooq; Abdulaqadir, Shang Ziyad; Hassan, Rawaz Rizgar; Hassan, Abdullah Othman (International Journal of Forest, Animal and Fisheries Research, 2021)
Heavy metals (Zn, Pb, Cu, Fe, Cd, and Ni) were measured seasonally in three different tissues (gonads, gills, and muscle) of common carp (Cyprinus carpio L., 1758) from the Taqtaq Region of the Little Zab River in Northern Iraq from March 2008 to February 2009. After wet digestion using the MALAIYANDI and BARETTE methods, heavy metals in fish samples were analyzed using atomic absorption spectrophotometry. To compare the data between seasons, age, sex, and size one-way ANOVA and principal component analysis were used (level of 0,05). In the sequence of Cyprinus carpio samples, mean concentrations decreased in the gonads and gills as Zn > Fe > Pb > Ni > Cu > Cd, and in the muscle as Zn> Pb > Fe > Ni > Cu > Cd. Heavy metal concentrations in the samples exceeded the tolerable limits set by international organizations (AIEA-407). Gills had the highest metal concentrations, followed by gonads and muscle. In the winter, the levels of heavy metals in carp tissues decreased. The average values of Zn (80,30 21,00 mg.kg) and Ni (6,95 0,19 mg.kg) were at their highest levels in spring, according to the results. In the winter, the highest Pb, Cu, and Fe levels were found to be 7,53 214, 5,31 0,03, and 22,12 16,06 mg.kg, respectively. Summer had the highest Cd levels, which were 3,29 0.69 mg.kg. Significant differences between seasons were found for each metal (P 0.05).